Polarization Property Associated with Surface Plasmon Resonance in a Palladium Thin-Film Coated Aluminum Grating in a Conical Mounting and Its Application to Hydrogen Gas Detection - Toyonori Matsuda; Isao Tsunoda; Shinichiro Koba; Yu Oshiro; Hiroyuki Odagawa (Sensors, 2024)
We have investigated a polarization property of the (specularly) reflected light from an aluminum grating, coated with a palladium (Pd) thin-film on its surface. The polarization property, which is associated with surface plasmon resonance (SPR), and occurs in the Pd thin-film on the aluminum grating in a conical mounting, is observed as a rapid change in the normalized Stokes parameter <semantics>s3,</semantics> around the resonance angle, <semantics>θsp</semantics>, at which point, SPR occurs. The sensing technique used the rapid change in <semantics>s3</semantics> to allow us to successfully detect a small change in the complex refractive index of the Pd thin-film layer upon exposure to hydrogen gas, with a concentration near the lower explosion level. Experimental results showed that the sensing technique provided a sensitive and stable response when the Pd thin-film layer was exposed to gas mixtures containing hydrogen at concentrations of 1 to 4% (by volume) in nitrogen.